Trans-perineal Prostate Biopsy under Trans-rectal Ultrasound Guidance - Xu, Hui; Lamichhane, Nirmal (Nepalese Journal of Cancer, 2019)
Prostate cancer is the most common cancer in males in the western world and is an emerging malignancy in eastern world as well. It is less invasive and easily curable in early stages. It requires efficient and accurate diagnosis strategy to detect it early. To date, the standard diagnosis procedure involves a blind biopsy with a high rate of false negative results. Trans-perineal prostate biopsy is re-emerging after decades of being an underused alternative to trans-rectal biopsy guided by trans-rectal ultrasonography. In order to overcome these limitations, the paper proposes the method and advantages of trans-perineal prostate biopsy.